Assessment of the Combined Effect of Epstein–Barr Virus and Plasmodium falciparum Infections on Endemic Burkitt Lymphoma Using a Multiplex Serological Approach - Aguilar, Ruth; Casabonne, Delphine; O’Callaghan-Gordo, Cristina; Vidal, Marta; Campo, Joseph J.; Mutalima, Nora; Angov, Evelina; Dutta, Sheetij; Gaur, Deepak; Chitnis, Chetan E.; Chauhan, Virander; Michel, Angelika; et al. (Frontiers in Immunology, 2017)
Epstein-Barr virus (EBV) is a necessary cause of endemic Burkitt lymphoma (eBL), while the role of Plasmodium falciparum in eBL remains uncertain. This study aimed to generate new hypotheses on the interplay between both infections in the development of eBL by investigating the IgG and IgM profiles against several EBV and P. falciparum antigens. Serum samples collected in a childhood study in Malawi (2005-2006) from 442 HIV seronegative children (271 eBL cases and 171 controls) between 1.4 and 15 years old were tested by quantitative suspension array technology against a newly developed multiplex panel combining 4 EBV antigens (ZEBRA, EA-D, EBNA-1 and VCA-p18) and 15 P. falciparum antigens selected for their immunogenicity, role in malaria pathogenesis and presence in different parasite stages. Principal component analyses, multivariate logistic models and elastic net regressions were used. As expected, elevated levels of EBV IgG (especially against the lytic antigens ZEBRA, EA-D and VCA-p18) were strongly associated with eBL (high versus low tertile odds ratios [OR]= 8.67, 95% confidence interval [CI]= 4.81-15.64). Higher IgG responses to the merozoite protein MSP-3 were observed in children with eBL compared to controls (OR= 1.29, 95%CI= 1.02-1.64), showing an additive interaction with EBV IgGs (OR= 10.6, 95% CI= 5.1-22.2, P= 0.05). Using elastic-net regression models, eBL serological profile was further characterized by lower IgM levels against P. falciparum pre-erythrocytic-stage antigen CelTOS and EBV lytic antigen VCA-p18 compared to controls. In a secondary analysis, abdominal Burkitt lymphoma had lower IgM to EBV and higher IgG to EA-D levels than cases with head involvement. Overall, this exploratory study confirmed the strong role of EBV in eBL, and identified differential IgG and IgM patterns to erythrocytic versus pre-erythrocytic P. falciparum antigens that suggest a more persistent/chronic malaria exposure and a weaker IgM immune response in children with eBL compared to controls. Future studies should continue exploring how the malaria infection status and the immune response to P. falciparum interact with EBV infection in the development of eBL.